A regulamentação das parcerias público-privadas (PPP) no Brasil e a experiência do Reino Unido - Archanjo, Paula Fajardo (2006)
The purpose of this dissertation is to analyse the Public Private Partnership (PPP) law in Brazil in comparison with the United Kingdom s Private Finance Initiative (PFI). The analysis considers the Brazilian federal law and São Paulo and Minas Gerais states law. The first PPP projects (which are in an advanced stage of development) include the construction of a new line in São Paulo s subway system, and the recovery and maintenance of a highway (MG-050) in Minas Gerais. Studying the law is useful for a better understanding of the implementation and operation of future projects in order to provide more effective public infra-structure services and goods. In an atmosphere of fiscal restraint or limited resources, PPP procurement process is an alternative to the provision of public infra-structure services provided by government alone. The analysis of the Brazilian laws incorporates many aspects of British experience, which will be considered as a model in looking at a number of projects and capital involved